Personalized Learning Environment (PLE) Integration In The 21st Century Classroom - Che Ku Mohd, Che Ku Nuraini; Shahbodin, Faaizah (Machine Intelligence Research Labs, 2015)
In the fast changing world of the early 21st century education is also changing. The use of ICT in education lends itself to more student-centred learning settings. Given this changing landscape of teacher education, the purpose of this paper is to explore new educational approaches to enhance teachers’ ICT capabilities in the 21st century learning environment. The literature indicates that a brief explanation of 21st century education about roles of (i) Student, (ii) Teacher,(iii) Curriculum, (iv) Classroom and (v) Information and Communication of Technology (ICT). The new approach in education nowadays introduced, which is Personalized Learning Environment (PLE). PLE enables learners to organize their learning, provides the freedom to choose content, and allows communication and collaboration with others easily. In conclusion, the paper concludes with recommendations for continued improvements in 21st century education in order to ensure the opportunities of higher education remain open to as many students as possible.